Intravenous Thrombolysis for Acute Ischemic Stroke in Patients With Cardiac Myxoma: A Case Series and Pooled Analysis - Jie Rao; Jie Rao; Zi Tao; Qiongqiong Bao; Mingxia Jiang; Enyang Zhou; Xueli Cai; Fangwang Fu (Frontiers in Neurology, 2022)
Background and PurposeAcute ischemic stroke (AIS) is a major life-threatening consequence of cardiac myxoma (CM) and leads to a poor prognosis. Although intravenous thrombolysis (IVT) is the first-line treatment for AIS, its efficacy and safety in CM-AIS have not been established. Currently, there are only limited data from case reports. Our study aimed to investigate the clinical characteristics of CM-AIS and evaluate the safety and efficacy of IVT for CM-AIS patients.MethodsFourteen CM-AIS patients who received IVT between January 2016 and December 2021 were identified from our multicenter stroke registry databases. Clinical, neuroimaging and outcome data were analyzed. We then performed a pooled analysis of the published literature from inception to December 2021.ResultsOf the 14 CM-AIS patients, nine were treated with IVT alone, and five were treated with bridging therapy (BT). The median age was 51.5 years, and 57.1% were female. The median onset-to-needle time was 160 min. The median National Institute of Health Stroke Score (NIHSS) decreased from 15.5 at presentation to 13 24 h after IVT. Very early neurological improvement (VENI) was observed in one patient. Hemorrhagic transformation (HT) was observed in five (35.7%) patients, and only one patient was symptomatic (7.1%). Three-month favorable outcomes were achieved in six patients (66.7%) who underwent IVT alone and three patients (60%) who received BT, which resulted in a total proportion of favorable outcomes of 64.3%. None of the patients died at 3 months follow-up. Forty-seven cases (15 BT patients) were included for the pooled analysis. The median NIHSS score was 16.5, and VENI was observed in 10 (21.3%) patients. HT was detected in 11 patients (23.4%), and four (8.5%) patients were symptomatic. Favorable outcomes at 3 months were achieved in 61.7% of patients, 56.3% of patients who underwent IVT alone, and 73.3% of patients who received BT. The 3-month mortality rate was 4.3%.ConclusionsIVT is a potentially safe and efficient treatment for CM-AIS patients. Further studies with larger sample sizes are required to provide more evidence on the safety and efficacy of IVT and BT in CM-AIS patients.